Follow-up Study of Microflora Changes in Crevicular Gingival Fluid in Obese Subjects After Bariatric Surgery - Balogh, Bettina; Somodi, Sándor; Tanyi, Miklós; Miszti, Cecília; Márton, Ildikó; Kelentey, Barna (Obesity surgery, 2020)
The objective of our study was to investigate the effect of weight loss on the crevicular microflora following bariatric surgery. Crevicular fluid samples were taken from 57 subjects: 22 were in the normal control group; 18 in the obese control group; and 17 patients had had bariatric surgery, who underwent a repeat sampling 6 to 12 months after the operation. Crevicular fluid samples were analyzed by MALDI-TOF MS analysis. After surgery and weight loss, the mean germ count increased, albeit not significantly. Also, Candida albicans and non-albicans Candida species: C. dubliniensis , C. kefyr , and C. lusitaniae appeared after surgery ( p < 0.05) in subjects where Neisseria was either absent throughout or eliminated after surgery. However, periodontitis did not develop during this time in our subjects.